2004
DOI: 10.1016/j.ydbio.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphic expression pattern of a splice variant of zebrafish vasa during gonadal development

Abstract: In Drosophila, the RNA helicase VASA (VAS) is required for both germ line formation and oocyte differentiation. While the murine VAS homologue is required for spermatogenesis, it is dispensable for germ line formation. The molecular basis for this apparently dual role of VAS in germ line ontogeny is, however, unclear. Recent evidence indicates that fish, like flies, employs VAS both in early and late stages of the germ line development and that there is a sex-linked differential expression of splice variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 31 publications
6
85
2
Order By: Relevance
“…Additionally, sexual dimorphic expression of vasa variants has also been reported. Zebrafish had long and short isoforms of vasa in the ovary, and only short transcript in the testis (Krovel and Olsen 2004), while the rare minnow had long and short variants of vasa in the testis, and only a long variant in the ovary (Cao et al 2012). In tilapia, vas and vas-s variants were both detected in the ovary and the testis, with vas mainly expressed in the testis and vas-s abundant in the ovary (Kobayashi et al 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, sexual dimorphic expression of vasa variants has also been reported. Zebrafish had long and short isoforms of vasa in the ovary, and only short transcript in the testis (Krovel and Olsen 2004), while the rare minnow had long and short variants of vasa in the testis, and only a long variant in the ovary (Cao et al 2012). In tilapia, vas and vas-s variants were both detected in the ovary and the testis, with vas mainly expressed in the testis and vas-s abundant in the ovary (Kobayashi et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Different isoforms of Vasa homologues have also been identified in other fish. Two vasa variants were found in tilapia (Kobayashi et al 2002), zebrafish (Krovel and Olsen 2004) and the rare minnow (Cao et al 2012), while more than two transcripts were characterized in Senegalese sole (Pacchiarini et al 2013), Japanese flounder (Wu et al 2014b), tongue sole and Lusitanian toadfish (UbedaManzanaro et al 2014). Most isoforms from each species displayed slight sequence differences at the N-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…The AB zebrafish strain and the Tg(vasa:vasa-egfp) zebrafish line of AB strain (78) were used for the temperature treatment experiments. Breeding protocols and husbandry details can be found in SI Appendix, Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, it was thought that Vasa expression in fish was restricted to germ cell lineage, however Vasa extragonadal expression has been reported in several fish species, such as Onco rhynchus mykiss (Yoshizaki et al 2000), Dicentrarchus labrax (Blázquez et al 2011) and Solea senegalensis (Pacchiarini et al 2013b). Many studies have reported levels and pattern changes of Vasa expression during embryogenesis, sex differentiation and larval development in various fish species (Yoon et al 1997, Krøvel & Olsen 2004, Xu et al 2005, Li et al 2010, Raghuveer & Senthilkumaran 2010, Cao et al 2012, Lin et al 2012, Pacchiarini et al 2013a, showing a differential expression during oogenesis and spermatogenesis (Cao et al 2012). Different Vasa transcripts with different expression patterns have also been characterized in diverse fish species, such as zebrafish, tilapia and Senegalese sole (Yoon et al 1997, Kobayashi et al 2002, Pacchiarini et al 2013b, and the Vasa gene is usually present as a single copy gene in the majority of chordates, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Different Vasa transcripts with different expression patterns have also been characterized in diverse fish species, such as zebrafish, tilapia and Senegalese sole (Yoon et al 1997, Kobayashi et al 2002, Pacchiarini et al 2013b, and the Vasa gene is usually present as a single copy gene in the majority of chordates, e.g. in zebrafish (Krøvel & Olsen 2004). However, recently, Fujimura et al (2011) re ported 3 Vasa gene loci in the genome of tilapia.…”
Section: Introductionmentioning
confidence: 99%